Agricultural Transition in Asian Mega Deltas - an interactive dialogue - CGIAR Initiative on Asian Mega-Deltas (2022)
To highlight the lessons learned, challenges ahead, and recommendations that could be taken into account for agricultural transformations in the Asian Mega-Deltas, the CGIAR Initiative on Securing the Food Systems of Asian Mega‐Deltas for Climate and Livelihood Resilience (AMD) and Wageningen University & Research (WUR) organized an interactive dialogue event, which is officially part of the Benelux/EIB Pavilion at the Sharm el-Sheikh Climate Change Conference (COP27).